Characteristics of Hepatitis C Epidemic Process in the Republic of Belarus - V. S. Vysotskaya; N. D. Kolomiets; E. L. Gasich; O. N. Hanenko; O. V. Tonko; I. N. Glinskaya; O. N. Romanova; A. N. Kabankova (Эпидемиология и вакцинопрофилактика, 2021)
Relevance. The medical and social significance of hepatitis C (HC) is determined by its widespread distribution, the involvement of the working-age population in the epidemic process, the multiplicity of transmission routes of the pathogen, a variety of clinical forms, and a high frequency of chronicity and malignancy of the process. The purpose of the study - to characterize epidemic process of HC in the Republic of Belarus, based on long-term observations. Materials and methods. Assessment of the incidence of HS in the population as a whole and in individual groups was carried out according to the data of the state statistical reporting form «Report on individual infectious, parasitic diseases and their carriers» in 1996-2019. Genotyping was carried out in the core/E1 and NS5B areas; for bioinformation analysis, BoiEdit v.7.2.5, SeqA6, SeqScape v.3, and Mega 6 were used. Statistical calculations were performed using the software Statistica V.6.1 (Statsoft, USA). Credibility of long-term assessment was proved using the Spearman correlation coefficient Rs. Results. The incidence of acute hepatitis during the 24-year epidemiological observation period decreased 3.5 times from 2.68 cases per 100 ths people in 1996 to 0.76 per 100 ths people in 2019. With a downward trend in number of carriers of hepatitis C -6.34% (p < 0.05) there is still a moderate upward tendency in the incidence of chronic hepatitis C (+4.37%, p < 0.05). The age group of 21-39 years is the main cohort in the structure of patients with acute hepatitis (1.1-2.5 per 100 ths). 68.8% of all patients with chronic as well as latently occurring forms of HC are people aged 21-49, the incidence in this age group ranges from 61.3-186.2 per 100 ths and exceeds 1.3-4.5 times the incidence among the total population of Belarus. During 2018-2019 among the selected isolates, the hepatitis C was dominated by the 1st genotype represented by 1a (10.3 ± 1.7%) and 1b (51.7 ± 2.9%) subtypes and genotype 3a (31.8 ± 2.7%). Conclusion. In the Republic of Belarus the decrease in the incidence of acute hepatitis (decrease rate of -6.09% p < 0.05) comes along with the increase in the incidence of chronic hepatitis C (increase rate + 4.37% p < 0.05). The main risk group for hepatitis C is 21-49 years old. Thus, the largest share (about 70%) of disease falls on socially active population in the reproductive age with the highest labor potential (21-49 years old). The proclaimed and widely manifested decrease in the incidence of acute hepatitis is shadowed by the continued growth of newly diagnosed chronic hepatitis C in high-risk groups and it will surely worsen epidemiological situation with a large number of chronic sources of infection. The results of molecular genetic monitoring show that in the period from 2018 to 2019 the genetic structure of hepatitis C virus isolates is not different to the period of 2004-2015, and the prevailing types are still the 1b, 1a, and 3a subgenotypes of Hepatitis C virus. This knowledge is necessary for the planning, implementation and development of the Program for Elimination of Hepatitis C in the Republic of Belarus for 2019-2028, which aims to reduce HC virus infection by its prevention, detection and antiviral treatment. An expected result of the Program is a substantial decrease in mortality, disability as well as long-term job disqualification among the population of the Republic of Belarus.